On improved RCM model to theart evaluation for radiation sesource - Zhang, Ying (Array, 2020)
Focusing on the deficiency of intuition, real-time and complexity of threat evaluation of radiation resource, an algorithm based on improved radar chart method (RCM) is proposed in this paper. In the algorithm proposed, coarse sorting is integrated with fine sorting to obtain a more accurate and reliable result of threat evaluation. Coarse sorting is applied to sequence all the radiation resource roughly according to radar operation mode, and reduce the task priority of low-threat radiation resource. Then, on the basis of improved RCM, fine sorting is applied to sequence the radiation resource with same radar operation mode. Finally, obtain the results of threat evaluation which combined coarse sorting with fine sorting. Simulation analysis shows the correctness and effectiveness of this algorithm. Comparing with classical method of threat evaluation of radiation resource based on RCM, the algorithm proposed in this paper is more visual in image and can work quickly with lower complexity.